P04.17 Cancer cell lines response to tumor treating fields: results of a meta-analysis. (19th September 2018) - Lavy Shahaf, G; Giladi, M; Schneiderman, R; Kinzel, A; Weinberg, U; Kirson, E; Palti, Y
Abstract: Background: Tumor Treating Fields (TTFields) therapy, an approved modality for the treatment of glioblastoma, is currently being investigated in many other indications. These alternating electric fields were shown to exert an inhibitory effect in numerous cancer cell lines with some variability in the response of different cell lines. The goal of the present study is to compare cell lines characteristics based on their response pattern to TTFields. Material and Methods: TTFields were applied for 72 hours at their optimal frequency with the same nominal intensity (1.7 V/cm) to forty different human cancerous cell lines. Cell survival and clonogenicity were determined. Functional analysis of differentially expressed genes and mutations associated with response to TTFields was performed based on data from the Cancer Cell Line Encyclopedia (CCLE) database. Sensitivity to TTFields was compared with pharmacological profiling (CCLE). Results: The inhibitory response to TTFields was found to be distributed around an average of 50% with a cytotoxic effects ranging between 14% and 86% reductions in cell counts, and a clonogenic effect ranging between no effect and 88% reduction in the number of colonies. In line with TTFields anti-mitotic properties, a correlation between treatment efficacy and cell doubling time was demonstrated. Yet, few cell lines demonstrated enhanced treatment efficacy despite long doubling time suggesting other factors may also be involved in the response to treatment. Functional analysis of cell line gene expression and mutation data revealed enriched pathways related to DNA damage repair response such as the BRCA1 repair pathway which validate previous data obtained using different methodologies. Other pathways which were found to be associated with sensitivity to TTFields include: cell migration, hypoxia signaling, oxidative stress. Pharmacological profiling based on IC50 values, revealed increased sensitivity to: Lapatinib, PHA-665752 and PLX-4720 within the group of cell lines which were less sensitive to TTFields. Conclusion: This multi parameter, large scale comparison of cancerous cell line response to TTFields demonstrate the broad effectiveness of TTFields in various cell lines and define the optimal frequency to be applied for each cell line. The data suggest that beside their anti-mitotic properties, TTFields may have effects on other cellular pathways. The pharmacological profiling may offer a rational for combining specific agents with TTFields in cells which are less sensitive to the electric fields.